Illegal Oil Drilling in the Theoretical View of Imam Ghazali - Nadia Ramadani; Dhiauddin Tanjung; Arifuddin Muda Harahap (Journal of Law, Politic and Humanities, 2025)
Illegal oil drilling is a phenomenon that is rampant in Indonesia and causes various negative impacts, such as environmental pollution, work accidents, social conflicts, and economic losses for the country. In Islam, every economic activity must take into account the principle of mashlahah put forward by Imam Al-Ghazali, which is to maintain the five main aspects of life (al-daruriyyat al-khamsah): religion (al-din), soul (al-nafs), intellect (al-aql), heredity (al-nasl), and property (al-mal). This study aims to analyze the practice of illegal oil drilling from the perspective of Imam Al-Ghazali's mashlahah theory to assess the extent to which these activities provide benefits or actually cause more damage (mafsadah). Through the conceptual approach and approach of Islamic law with the method of literature study, this study found that illegal oil drilling caused more mafsadah than mashlahah. This activity is contrary to the principle of life protection due to the high risk of accidents, damaging the environment that has a bad impact on future generations, and causing economic losses that harm the state and society. Therefore, from the perspective of mashlahah, illegal oil drilling cannot be justified and must be prevented through stricter policies, strict law enforcement, and economic empowerment of the community so that it does not depend on illegal activities